2015
DOI: 10.1089/scd.2014.0588
|View full text |Cite
|
Sign up to set email alerts
|

VAV3 Overexpressed in Cancer Stem Cells Is a Poor Prognostic Indicator in Ovarian Cancer Patients

Abstract: Ovarian carcinoma is a highly lethal malignancy due to frequent relapse and drug resistance. Cancer stem cells (CSCs) are thought to contribute significantly to disease relapse and drug resistance. In this study, a subpopulation of CSCs of ovarian carcinoma was isolated and the genes differentially expressed in these cells were identified to characterize CSCs and to find candidate biomarkers. Ovarian carcinoma cells from patients were primarily cultured, and spheroid-forming cells (SFCs) were isolated. The cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 46 publications
5
17
0
Order By: Relevance
“…Gene array analyses revealed significant differences in expression of several genes, whereby two candidate genes, namely ABCB1 and Vav3, exhibited marked overexpression in the stem‐cell like side‐population. This finding is in line with a recent study showing that Vav3 is overexpressed in spheroid‐forming ovarian cancer cell populations expressing stem cell markers such as ALDH1, CD44 and CD133 . In our study, Vav3 protein was shown to be associated with distant metastasis and poor clinical outcome in a collective of 74 cancer specimens.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Gene array analyses revealed significant differences in expression of several genes, whereby two candidate genes, namely ABCB1 and Vav3, exhibited marked overexpression in the stem‐cell like side‐population. This finding is in line with a recent study showing that Vav3 is overexpressed in spheroid‐forming ovarian cancer cell populations expressing stem cell markers such as ALDH1, CD44 and CD133 . In our study, Vav3 protein was shown to be associated with distant metastasis and poor clinical outcome in a collective of 74 cancer specimens.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in line with a recent study showing that Vav3 is overexpressed in spheroid-forming ovarian cancer cell populations expressing stem cell markers such as ALDH1, CD44 and CD133. 45 In our study, Vav3 protein was shown to be associated with distant metastasis and poor clinical outcome in a collective of 74 cancer specimens. In our cohort full-length Vav3 was not associated with clinical outcome, whereas Vav3.1 overexpression was linked to clinicopathologically tumor variables and was also prognostically relevant.…”
Section: Increased Vav31 Expression In Platinum-refractory Patientsmentioning
confidence: 56%
“…Their anomalous expression and/or activation may impact patient outcome prediction and therapeutic management. For example, Vav3 overexpression in ovarian cancer associates with poor prognosis and confers resistance to established therapeutic regimes (31). Genetic alterations in the VAV1 gene, including activating mutations and fusions, have been found in peripheral T-cell lymphomas, establishing an oncogenic role for this GEF in the development of this disease (32).…”
Section: Emerging Paradigms In Rho Gtpase Hyperactivation In Cancermentioning
confidence: 99%
“…Through comprehensive integration of references about CSC and drug resistance in PubMed, we summarized 36 CSC genes significantly associated with drug resistance in ovarian cancer, which included POU5F1 , [3] ENG , [4] ABCB1 , [5] ABCG2 , [6] ALDH1A1 , [7] ARID3B , [8] PROM1 , [9] CD44 , [10] KIT , [11] MAPK1 , [12] EDNRA , [13] EZH2 , [14] TERT , [15] JAK2 , [16] KLF5 , [17] LIN28A , [18] MMP2 , [19] MYD88 , [20] NACC1 , [21] NANOG , [22] NFKB1 , [23] NOTCH3 , [24] TP53 , [25] PIK3CA , [26] SOX2 , [27] TLR2 , [28] TWIST1 , [29] VAV3 , [30] WG , [7] XIAP , [31] YAP1 , [32] FLT4 , [33] NES , [34] CD24 , [35] WWOX , [36] and DDB2 . [37] …”
Section: Resultsmentioning
confidence: 99%
“…However, cisplatin resistance is a serious issue that greatly affects the survival of patients. Several studies have found the evidence of the existence of CSC in many tumors, such as pancreatic cancer, [40] ovarian cancer, [30] and liver cancer. [41] CSCs are the origins of variety of cancer cells, they can be primary resistance to the traditional treatment or acquired resistance after the initial treatment.…”
Section: Discussionmentioning
confidence: 99%